Product Design and efficient Management of Recycling and Waste Treatment - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1999)
Using a general equilibrium model where material is first extracted, then used for producing a consumption good, recycled and finally treated to reduce environmental damage, we study efficiency-restoring policies, when one or more of the constituent markets are inactive. The material is modeled as being embodied in the output and forms an important aspect of green product design. If all markets for embodied material per unit output fail and if recycling benefit exceeds environmental damage, the policy instruments needed for green design are a tax on the consumption good supply and a subsidy on the demand for material input.
Keywords: 330